2020
DOI: 10.1007/s11135-020-01057-8
|View full text |Cite
|
Sign up to set email alerts
|

Analyses the effects of COVID-19 outbreak on human sexual behaviour using ordinary least-squares based multivariate logistic regression

Abstract: This study aimed to evaluate the impact of COVID-19 on sexual, mental and physical health. There were 262 respondents included in this study (38% female and 62% male) above 18 years of age from India. Statistical analysis was performed using Ordinary Least Squares (OLS) based on multivariate logistic regression analysis. The numerical tests were performed by using Python 3 engine and R-squared (coefficient of multiple determinations for multiple regressions) for prediction and P value > 0.5 is considered to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 18 publications
0
27
0
4
Order By: Relevance
“…For that reason, the promotion of protective factors for mental health could lead to the development of tailored strategies focusing on physical activity and an active and healthy sexual life during the whole cycle of life, due to the potential relationship of these variables. Another implication, also highlighted in another study, should be the need to focus on enhancing sexual wellness by educating on and supporting sexual activities during the implementation of movement control measures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For that reason, the promotion of protective factors for mental health could lead to the development of tailored strategies focusing on physical activity and an active and healthy sexual life during the whole cycle of life, due to the potential relationship of these variables. Another implication, also highlighted in another study, should be the need to focus on enhancing sexual wellness by educating on and supporting sexual activities during the implementation of movement control measures [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…After assessing the full text of 38 articles, 17 articles were deleted for various reasons. Finally, 21 articles were included based on the above-mentioned inclusion criteria [26,28,37,[43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. All these studies were investigations with convenience samples that reported data at two time points.…”
Section: Study Selectionmentioning
confidence: 99%
“…Indeed, some studies have even reported positive sexual outcomes during the pandemic. For example, in Arafat et al's (2020) study, 50% of participants reported positive changes in their sex lives, Yuksel and Ozgor (2020) reported significantly higher levels of sexual desire and intercourse frequency (in two independent samples of women), Mahanty et al (2021) noted reports of increased sexual frequency in women, and Li et al (2020b) reported increases in masturbation frequency. In addition, in Lehmiller et al's (2021) study, almost 14% of the sample reported that their sex lives had improved, with one in five participants stating that they had added new activities to their repertoire of sexual behaviors.…”
Section: Introductionmentioning
confidence: 95%